Problems of Moodle-Based Learning Management System Development in Improving Lecturers' Professional Competence - Nona Kumala Sari; Moh Sain; Asmariani Asmariani (STAI Serdang Lubuk Pakam, 2023)
The Covid-19 pandemic brought changes to the implementation of lecturer certification. But change is not always taken for granted, there are several problems. This study aims to analyze the problems of developing a moodle-based learning management system in increasing the competence of professional lecturers. This research focuses on three things, namely on the use, impact and problems in its development. The research method used is qualitative with a case study approach, with research informants, professional lecturer competency training participants at UIN Sultan Syarif Kasim Riau. Collecting data using observation, interviews, and documentation studies. The results of the study reveal that the learning management system is used as a virtual learning platform that allows participants to access and read learning resources, discuss and carry out assignments. A significant impact on the increase in professional competence is realized from the higher mastery of lecture material, and the increase in the technological competency of the participants. Problems faced such as difficulty adapting, network damage, difficulty understanding information. This research certainly has implications as a reference for UIN Sultan Syarif Kasim Riau, especially in improving the quality of training.